2022
DOI: 10.3390/vaccines10020220
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Anti-SARS-CoV-2 Antibodies in Benadir Region, Somalia

Abstract: Only little is known about the true extent of COVID-19 in Somalia. The study aims to assess the seroprevalence of the COVID-19 pandemics in the Benadir region using SARS-CoV-2 antibodies and estimate the number of inhabitants infected with SARS-CoV-2. Population-based cross-sectional survey was conducted to measure the seroprevalence of antibodies against SARS-CoV-2 in the Benadir region (Mogadishu city). In the study, we enrolled 2500 Mogadishu city residents aged ≥18 years who did not receive the SARS-CoV-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
5
9
0
Order By: Relevance
“…A similar decreasing trend of seropositivity was reported in a population-based household survey in Nigeria, while in Cameroon an increasing trend was reported [ 4 , 29 ]. As reported by studies in Africa, Europe, and Asia, we observed a trend of increased seroprevalence with age, with older participants being more likely seropositive [ 3 , 20 , 22 , 28 , 30–32 ]. The lowest seroprevalence (67.7%) was recorded in participants <10 years of age, while the odds of seropositivity doubled in those aged 10–14 years.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A similar decreasing trend of seropositivity was reported in a population-based household survey in Nigeria, while in Cameroon an increasing trend was reported [ 4 , 29 ]. As reported by studies in Africa, Europe, and Asia, we observed a trend of increased seroprevalence with age, with older participants being more likely seropositive [ 3 , 20 , 22 , 28 , 30–32 ]. The lowest seroprevalence (67.7%) was recorded in participants <10 years of age, while the odds of seropositivity doubled in those aged 10–14 years.…”
Section: Discussionsupporting
confidence: 82%
“…However, antibodies directed against the SARS-CoV-2 nucleocapsid protein are known to wane over time, inducing underestimation of seroprevalence [ 25 , 26 ]. Lower seroprevalence estimates have been reported in Nigeria (42.5% in urban areas vs 53.5% in rural areas) and Somalia (44.8%), where less sensitive anti-spike protein–detecting lateral flow assays were used [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the WHO COVID-19 dashboard (16 May 2022), a total of 521,694,216 confirmed cases and 6,274,111 deaths have been reported globally [ 1 ]. Unfortunately, the burden of the disease is projected to continue to rise driven by community transmission by asymptomatic individuals [ 2 , 3 ]. The initial efforts to stem the tide and flatten the number of confirmed COVID-19 cases and death included both therapeutic and nontherapeutic measures [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, cases have in recent months increased tenfold, and there are indications of community transmission beyond the major cities 7. The risk of acquiring COVID-19 is known to be higher among the elderly as well as individuals with underlying comorbidities, including moderate to severe asthma, diabetes, cardiovascular diseases and other respiratory illnesses, including pregnancy which predisposes to severe illness 8–10. The pandemic has disproportionately impacted vulnerable groups such as persons with disabilities and internally displaced people (IDP) living in makeshift camps in Somalia.…”
Section: Introductionmentioning
confidence: 99%